Developing primary school students’ language skills from a critical thinking perspective: a methodological system - Almukhanbet, Sholpan; Moldabek, Kulakhmet; Orynbassarova, Gulzhan; Yesnazar, Assel; Zhorabekova, Ainur (Frontiers in Education, 2025)
This study focuses on developing the skills of primary school students to prepare them for the challenges of the 21st century, enabling them to be literate, capable of engaging in culturally sophisticated communication, thinking critically, solving problems, and productively creating projects. The primary goal is to propose a methodological system for developing language skills in primary school students through the lens of critical thinking. The components of this model—such as objectives, active learning tasks, teaching methods, technologies, forms, digital resources, content of the elective course, and expected outcomes—serve as the foundation for identifying possibilities to cultivate students’ language skills. One of these possibilities involves the design and implementation of the elective course “Linguistic Skills.” This course is designed to enhance students’ linguistic competencies through critical thinking-based approaches, utilizing integrated learning methods that incorporate cross-disciplinary themes.